Способ компенсации погрешности измерения ультразвукового локатора - Солдатов А. И. Алексей Иванович; Солдатов А. А. Андрей Алексеевич; Шульгина Ю. В. Юлия Викторовна; Дичев Н. В. Никита Владимирович
опубл. 20.03.15